Cadmium Uptake in Synechococcus aquatilis (Reynaud) Strain SY01 - Vallarta Jr., Ruperto; Cao, Ernelea; Sibal, Yvette Rosario (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Cadmium uptake in Synechococcus aquatilis (Reynaud) Strain SY01 showed a biphasic behavior, with an initial rapid passive cell wall interaction phase and a later slow intracellular cation uptake process. The cell wall uptake process followed Michaelis-Menten kinetics. The apparent K m of the uptake system was 38.89 µM, a relatively high affinity K m value compared to other metal uptake systems. Fitting of experimental data to the Langmuir and Freundlich adsorption isotherms showed that binding of cadmium to the cell surface was monolayer and/or multilayer, although the monolayer adsorption was more probable, as exemplified by a high correlation coefficient. This could be explained by the presence of a strong primary binding site which was responsible for a monolayer adsorption and a weak secondary binding site which could be responsible for a multilayer adsorption. The uptake process was found to be relatively specific for cadmium. Equimolar amounts (200 µM) of cobalt, nickel, magnesium, and copper did not significantly affect cadmium uptake. Synechococcus aquatilis Strain SY01 cells also showed an efflux mechanism for cadmium, although the amount of excluded cadmium was insignificant compared with the amount of adsorbed cadmium in the cell wall.
Keywords: kinetics; adsorption; cadmium; Synechococcus; cell wall